Gradient of luminal narrowing of internal carotid artery on atherosclerotic plaque as risk factor for cerebral ischemic damage - W. Yu. Ussov; A. S. Maksimova; V. E. Sinitsyn; S. I. Karas; E. E. Bobrikova; S. P. Yaroshevsky; O. I. Belichenko; N. M. Fedotov (Российский кардиологический журнал)
Aim. To study the clinical significance of the gradient of narrowing of arterial lumen (GNL) for atherosclerotic stenosis of the internal carotid artery (ICA) as a risk factor for ischemic brain damage.Material and methods. We proposed a new parameter of hemodynamic severity of ICA atherosclerotic stenosis — GNL. It calculated as ratio of the difference in the ICA cross section areas on the stenotic lesion and the near non-stenotic region to the distance between them: Snorm — Sstenosis)/Dnorm — stenosis, mm2 /mm. We examined 25 patients with advanced atherosclerosis and with uni(n=22) or bilateral (n=3) ICA stenosis >50% according to European Carotid Surgery Trial, and 11 individuals without ICA stenosis. Each participant underwent magnetic resonance angiography (MRA) of the carotid arteries with reconstruction of the arteries from C6-C7 level to the parietal bones, and the GNL was calculated. The thickness of the baseline slice was 0,8-1 mm. Each subject also underwent cerebral magnetic resonance imaging (MRI) in T1-, T2-, PD-, flair-weighted protocols. Results. Patients were divided into groups: group 1 (n=12) — without ischemic injury in the ICA system, and group 2 (n=13)  — with MRI signs ischemic injury history. The groups did not differ in proportion of stenosis (74,9±4,25% and 77,8±3,8%, p<0,05), ICA lumen area on the stenotic lesion (1,05±0,18 mm2 and 1,14±0,17 mm2 , p<0,05) and the ICA diameter at the non-stenotic region (4,30±0,32 mm and 4,9±0,29 mm, p<0,05). In control group, GNL was <0,75 mm2 /mm. Groups 1 and 2 significantly differed (2,47±0,41 mm2 /mm and 4,60±0,51 mm2 /mm, p<0,02). In group 2, 12 out of 13 patients had GNL >3,35 mm2 /mm, and, in group 1, 9 out of 12 — less than 3,35 mm2 /mm. GNL did not correlate significantly with other parameters of ICA stenosis. Two patients with the highest GNL in each group (5,5 and 8,6 mm2 /mm) had a fatal ischemic stroke within six monthsConclusion. Firstly, proposed parameter of stenosis hemodynamic severity GNL is independent, informative and prognostically important indicator for carotid artery atherosclerotic lesion.